1969
DOI: 10.1111/j.1476-5381.1969.tb09519.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of adrenal hormones in the synthesis of noradrenaline in cardiac sympathetic neurones

Abstract: . Adrenalectomy or adrenal demedullation affected neither the levels of endogenous catecholamines in the rat heart nor the accumulation of 3H‐noradrenaline 1 hr after its intravenous administration. . Twenty‐four hours after intravenous administration of labelled amine, however, its retention was markedly reduced in the heart of adrenalectomized or demedullated rats. Ganglionic blockade prevented this reduction. . Rate calculations from the decline of catecholamine levels after blockade of synthesis with α‐met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1972
1972
1986
1986

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 12 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…The work of both Neff et al (1968) and Bhagat ( 1969) has suggested that cardiac sympathetic nerve activity increased after adrenal medullectomy in the rat, indicating that there may be a compensatory sympathetic activation after medullectomy. The lack of alteration in excreted noradrenaline by MDX-group C rats does not necessarily preclude regional alterations in peripheral tissue sympathetic activity.…”
Section: Discussionmentioning
confidence: 97%
“…The work of both Neff et al (1968) and Bhagat ( 1969) has suggested that cardiac sympathetic nerve activity increased after adrenal medullectomy in the rat, indicating that there may be a compensatory sympathetic activation after medullectomy. The lack of alteration in excreted noradrenaline by MDX-group C rats does not necessarily preclude regional alterations in peripheral tissue sympathetic activity.…”
Section: Discussionmentioning
confidence: 97%